The immediate influence of various whole-body vibration frequency on balance and walking ability in children with cerebral palsy: a pilot study - Han, Yong-Gu; Lee, Soon-Won; Yun, Chang-Kyo (Journal of exercise rehabilitation, 2019)
The purpose of this pilot study is to examine the immediate effect of in-terventions based on the frequency of whole-body vibration on children with cerebral palsy’s balance and walking abilities. A total of 12 were selected as subjects. All subjects measured 10-m walking test (10MWT), Timed Up and Go (TUG) test and measured sway length (SL) and limit of stability (LOS) by bio-rescue. And those were performed again after the frequencies of the 12, 18, and 26 Hz were applied respectively. To check the immediate effect, all subjects performed only one frequency of in-terventions per day and no other treatment was performed in parallel to control the foreign variables. After intervention, 10MWT were signifi-cantly increased in the 12 and 18 Hz groups (P<0.05). TUG test and LOS were significantly increased in the 18 Hz group (P<0.05). There were no significant differences on TUG, SL, and LOS in the 12 Hz group. There were no significant differences on 10MWT, TUG, SL, and LOS in the 26 Hz group. Looking at the results of this study, the immediate effect of whole-body vibration shows that the frequency of the 18 Hz group is the most effective interventions in promoting walking and balancing abili-ties in children with cerebral palsy than frequencies of the 12 and 26 Hz groups.